DEPRESSION IN DIABETIC FOOT ULCERATION: THE ROLES OF HEALTH LITERACY, PERCEIVED WOUND SEVERITY, AND RESILIENCE - Adiyanto, Lelik (Journal of Applied Health Management and Technology, 2025)
Depression is a prevalent psychological comorbidity among patients with Diabetic Foot Ulcers (DFUs), significantly hindering wound healing and diminishing quality of life. This study aimed to analyze the influence of health literacy and patient perception of wound stage on depression, with resilience acting as a mediating variable. Employing a quantitative approach, the research utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) for analysis. A sample of 102 DFU patients was recruited from wound care networks in the Central Java region. The findings revealed that health literacy significantly impacted resilience (F² = 0.238) and directly contributed to reduced depression levels (F² = 0.205). Patient perception of wound stage also demonstrated a moderate influence on resilience (F² = 0.203) and a strong influence on depression (F² = 0.500). Resilience itself exhibited a moderate effect on depression (F² = 0.213). Mediation analysis indicated that both health literacy and perception of wound stage indirectly affected depression through resilience, with a p-value < 0.05 for both mediation pathways. In conclusion, this study demonstrates that health literacy and the perception of wound condition significantly influence the level of depression in DFU patients, both directly and indirectly through the mediation of resilience. Enhancing health literacy and fostering a positive perception of the wound through psychosocial approaches can be crucial strategies in mitigating the risk of depression. Furthermore, interventions aimed at strengthening resilience should be integrated into DFU care programs to improve the mental well-being and overall quality of life of these patients.